2011
DOI: 10.1002/jor.21349
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of TNF‐α, IL‐1β, and HIF‐1α on MMP‐2 production in ACL fibroblasts under mechanical stretch: An in vitro study

Abstract: ABSTRACT:The dynamics between inflammatory factors, mechanical stress, and healing factors, in an intra-articular joint, are very complex after injury. Injury to intra-articular tissue [anterior cruciate ligament (ACL), synovium] results in hypoxia, accumulation of various pro-inflammatory factors, cytokines, and metalloproteases. Although the presence of increased amounts of matrix-metalloproteinases (MMP) in the joint fluid after knee injury is considered the key factor for ACL poor healing ability; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Inflammatory cytokines, including IL-1β and TNF-α are involved in the up-regulation of MMPs (18,19). MMPs mediate connective tissue breakdown (11) and the degradation of numerous extracellular matrix proteins (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cytokines, including IL-1β and TNF-α are involved in the up-regulation of MMPs (18,19). MMPs mediate connective tissue breakdown (11) and the degradation of numerous extracellular matrix proteins (42).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies on human mesenchymal stem cells (hMSCs) revealed that expression of the master transcription factor for osteoblast differentiation, runt-related transcription factor 2 (RUNX2), was enhanced in the presence of media pre-conditioned with increased pro-inflammatory cytokine levels from classically activated monocytes (16,17). By contrast, inflammatory stimuli additionally induced factors that facilitate bone resorption, including matrix metalloproteinases (MMPs) in PDL fibroblasts (18) and the anterior cruciate ligament (19). In vitro (20) and in vivo (21,22) studies have demonstrated that alveolar bone resorption is closely associated with MMP production.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our results in the low dose MSC group demonstrating a smaller wound size and less creeping holds promise for stronger ligaments. Inflammatory cytokines, such as IL-1β, are known to activate matrix metalloproteinases (MMPs) in tendon and ligament leading to remodeling activity (32,33). The increased pro-inflammatory cytokines at day 5, including IL-1β, seen in the high dose MSC ligaments correlated with a larger healing region and active tissue seen later during healing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that TNF-α can not only induce the expression of MMP-2 and 9 [41,42], but also promotes the activation of pro-MMP-2 [43] and thereby enhances the activity of MMP-2 [41,44]. Additionally, both TNF-α and TNF-β can promote the activation of pro-MMP-9 [45].…”
Section: Role Of Mmp-2 and Mmp-9 In Chronic Kidney Disease (Ckd)mentioning
confidence: 99%